The unofficial guide to flipping properties - Richmond, Peter A. (Wiley Publishing, Inc., 2007)
You with everything from choosing and redoing the right house or condo to selling it for maximum profit. With tips from experienced flippers, it includes: Vital Information on finding and financing the right property; Insider Secrets on using and leveraging someone else's money; Money-Saving Techniques such as refacing or painting cabinets and updating the hardware; Time-Saving Tips such as consolidating your purchases (appliances, materials, tools, etc.) at a home improvement center; The Scoop on staging a property inside and out for maximum impact; Expert Advice to help you assess a property's profitability, set and monitor your budget, and more.